2012
DOI: 10.1021/jp3025478
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Monocrystalline Nanoflowers for Highly Efficient Magnetic Hyperthermia

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
260
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(278 citation statements)
references
References 51 publications
(71 reference statements)
13
260
1
4
Order By: Relevance
“…An enhanced SLP value of 1175 Wg -1 has been found for maghemite nanoclusters under an alternating magnetic field of 21.5 kAm -1 (at a frequency of 700 kHz) [30]. This value is similar to that observed for nanocrystals of enhanced magnetic anisotropy (nanocubes of 20 nm) [60].…”
Section: Nanoclusters As Heat Mediators In Magnetic Particle Hyperthesupporting
confidence: 76%
See 3 more Smart Citations
“…An enhanced SLP value of 1175 Wg -1 has been found for maghemite nanoclusters under an alternating magnetic field of 21.5 kAm -1 (at a frequency of 700 kHz) [30]. This value is similar to that observed for nanocrystals of enhanced magnetic anisotropy (nanocubes of 20 nm) [60].…”
Section: Nanoclusters As Heat Mediators In Magnetic Particle Hyperthesupporting
confidence: 76%
“…In a fashion analogous to the evolution of MRI relaxivities, a range of morphologies (Figure 20), associated with different magnetic material volume fractions, variable strength dipolar interactions, and emerging microscopic mechanisms (see Section 3.2) were shown to impact heat release. The SLP has been found enhanced compared to that of individual nanocrystals when superparamagnetic nanoclusters were capped with amine [30], while the opposite effect was observed for superparamagnetic nanocrystals embedded in polystyrene (PS) nanospheres [145]. Calculation of Néel and Brown relaxation times in the latter unveiled that the Néel relaxation is faster than the Brownian and shorter than the measurement time [145].…”
Section: Nanoclusters As Heat Mediators In Magnetic Particle Hyperthementioning
confidence: 98%
See 2 more Smart Citations
“…Using a CeO 2 matrix Abiade et al [24] were able to show that small nanoparticles (8 nm) could be tuned to have a T B higher then room temperature and that this was related to the interparticle spacing. Recent work on flower-like maghemite nanoparticles showed that the blocking temperature of iron oxide nanoparticles could be greatly enhanced if mutli-core particles were created [26,27]. It was thought that magnetic exchange between the surfaces of each particle led to an overall increase in magnetic anisotropy and a hardening of the particles.…”
Section: Samples 1 2 Andmentioning
confidence: 99%